Self-Efficacy in Writing the Final Research Report among EFL Undergraduate Program Students - Andini Putri Utami; Murni Mahmud; La Sunra (International Journal of Language, Education, and Literature, 2025)
Self-efficacy is the theory by Bandura (1986), it refers to an individual's belief in their ability to accomplish specific tasks. This study aims to explore undergraduate student’ self-efficacy regarding the levels and perception in writing the final research report. The researcher applied mixed-method to achieve the research objectives. The data were collected through questionnaire and semi-structured interview. The participants were 30 students of English Language Education Undergraduate Program of Universitas Negeri Makassar in the academic year of 2021/2022 to conduct the questionnaire and six students for the interview. The result of the study reveal that most undergraduate students have moderate to high levels of self-efficacy in using artificial intelligence (AI) tools to write final research reports. This result reflects a fairly strong belief in facing academic challenges, particularly in the final research report. Furthermore, the students perceived that they often used artificial intelligence tools with the various types based on their needs. They also perceived that AI contribute to writing the final research report, including generates ideas, solve the language and grammar problems, provide relevant literature, and as a supporting tool but not replace the human effort to thinking. In addition, this study is only limited to one education levels, it is recommended for the next researches to study more participants from different backgrounds and also explore the influence of AI on other aspects.